Tailored material flow in pin-extrusion of sheet metal under varying material and geometric conditions for enhanced joining technology applications - Römisch, David; Kraus, Martin; Merklein, Marion (International Journal of Material Forming, 2025)
Pin structures extruded from the sheet metal plane have numerous industrial applications. For instance, they can be used in bulk microforming to solve handling difficulties or in joining technology to connect dissimilar materials to overcome challenges of different chemical, thermal and mechanical properties of materials. Due to the absence of material flow restrictions in the direction of the sheet metal plane, pin extrusion is affected by numerous process-, workpiece- and tool-related parameters, which have a huge impact on the material utilization and the obtainable pin geometry. Within the scope of this study, a combined numerical-experimental research approach is used to analyze the influence of the material and its condition on the achievable pin height and the occurrence of the mostly undesired funnel formation at high punch penetration depths. For this purpose, elastic-ideal plastic and elastic-real hardening model materials are first investigated numerically, which are subsequently validated and verified in experiments by using the materials Cu-OFE and DC04 on a laboratory scale. Based on the results, recommendations for the material selection and its properties are derived in order to maximize the material utilization. In addition, a pin joining process with locally modified extrusion conditions to increase the load-bearing capacity, especially under axial load, is being investigated with DP600 and AA 6014-T4. This process is a new type of two-stage mechanical joining process without an auxiliary joining element in which pin structures extruded from the sheet metal plane are used to join dissimilar materials in a subsequent step. In this work, test specimens are locally pre-punched before pin extrusion to create an enhanced pin geometry in order to achieve an improved undercut in the subsequent joining process. As a result, a new type of pin geometry was realized and investigated, which shows a significant increase of up to 82% in load-bearing capacity under axial load compared to the existing reference pin geometr
Keywords: Pin extrusion; Material flow; Pin-joining; Sheet metal